Forest habitats on the territory of the National Park „Central Balkan" Bulgaria - Nikolov, Ivaylo Dimitrov; Dimitrov, Marius Alipiev (Hacquetia, 2023)
Identifaction and characterization of forest habitats on the territory of the "Central Balkan" National Park in Bulgaria was carried out. The national park is one of the most valuable and largest protected areas in Europe – second category according to the International Union for Conservation of Nature (IUCN). Based on 786 phytosociological relevés, a total of 17 different habitat types, according to EUNIS were identified and mapped. The habitats were ecologically characterized by Ellenberg indicator values and their area was determined. A comparison was made with the areas determined in previous works. The applied method is suitable for the purposes of managing protected territories and zones, for monitoring the status and especially the conservation status of the habitats. The results and especially the established new habitats support this point of view.